The Urgency of Environmental Adaptation Skills in Early Childhood: A Literature Review - Redinanti, Dian Putri (Exploration in Early Childhood Research, 2024)
Early childhood children face a dynamic and constantly changing environment. The ability to adapt to the environment at this stage is an important key in their development. This research explores the urgency of environmental adaptability in early childhood in the context of their holistic development. Through a literature review, it is known that environmental adaptability influences various aspects, including cognitive, social, emotional and physical. Children who are able to adapt to their environment tend to have better social adjustment, better learning abilities, and higher levels of overall well-being. Research also highlights factors that influence the ability to adapt to the environment in early childhood, such as family support, interactions with peers, availability of resources, and personal experiences. It was found that an environment that is supportive, responsive and provides appropriate challenges can improve children's adaptive abilities. In conclusion, understanding the urgency of environmental adaptability in early childhood is important to inform effective educational and parenting practices. Interventions that strengthen early childhood adaptation abilities can provide a solid foundation for optimal development in the future. Therefore, research and practice that focus on building environmental adaptation capabilities at this stage need to be given serious attention.